Epilepsia refratária do lobo temporal em associação com lesões estruturais - Meguins, Lucas Crociati (2017)
To present a surgical series of patients with intractable epilepsy associated with low grade temporal gliomas, neurocysticercosis and cavernous malformation. Method: A retrospective study was conducted in the Hospital de Base, from São José do Rio Preto, São Paulo. Results: Regarding patients with low grade temporal gliomas, sixty five patients were operated in our institution. Males were more affected than females and the mean age at surgery was 32.3 ± 8.4 (9-68 years). The mean age at seizure onset was 25.7 ± 9.2 (11-66 years). Seizure outcome was classified according with Engel classification. After one year of follow up, forty two patients (64.6%) were Engel I; seventeen (26.2%) Engel II; four (6.2%) Engel III and two (3.1%) Engel IV. Statistically significant difference in seizure outcome was obtained when comparing the extension of resection. Engel I was observed in 39 patients (69.6%) with total resection and in only 3 (33.3%) patients with partial resection. Regarding patients with temporal lobe epilepsy associated with hippocampal sclerosis and neurocysticercosis, 79 (62.2%), 37 (29.1%), 6 (4.7%), and 5 (3.9%) patients were Engel class I, II, III, and IV, respectively. Fifty-two (71.2%) patients with epilepsy durations ≤ 10 years prior to surgery were seizure-free one year after the operation compared to 27 (50.0%) patients with epilepsy durations > 10 years (p = 0.0121). Forty-three (72.9%) patients with three or fewer lobes affected by NCC were seizure-free one year after the operation, and 36 (52.9%) patients with more than three involved lobes were seizure-free after surgery (p = 0.0163). Regarding patients with temporal lobe epilepsy associated with mesiotemporal cavernous malformation, a total of 21 patients were included in the study. Thirteen patients (62%) evolved to Engel I; 5 (24%) to Engel II, 2 (10%) to Engel III, and 1 (5%) to Engel IV. We observed that 10 (48%) patients with 12 years or less of epilepsy duration evolved to Engel I and 1 (5%) to Engel II; whereas from a total of 10 patients with epilepsy duration of more than 12 years, 3 (30%) evolved to Engel I and 7 (70%) to Engel II, III, or IV (P < 0.001 [bilateral]; P1 ≠ P2) .Conclusion: In the present study, we observed that (1) gross-total resection of temporal low grade gliomas is a critically important factor in achieving seizure-freedom, (2) longer epilepsy durations and multiple lobe involvement predicted worse seizure outcomes in temporal lobe epilepsy associated with hippocampal sclerosis and neurocysticercosis patients and (3) postsurgical seizure outcome for temporal lobe epilepsy associated with mesiotemporal cavernomas is satisfactory and with better results when performed early on the disease course.